HUBUNGAN ANTARA BELIEF DAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII MTS NEGERI 1 PONTIANAK - Wittia Rosi Rahayu; Mohamad Rif'at; Hamdani Hamdani (UNIVERSITAS TANJUNGPURA, 2022)
AbstractThis study intends to decide the connection among Conviction and Arithmetic Learning Results. This exploration utilizes ex post facto technique and type of correlational examination. The example in this review was class VII understudies, the information acquired in this review were the consequences of a numerical conviction survey and the benefit of learning results. In view of the consequences of the measurable trial of Pearson connection investigation utilizing SPSS 26, it was gotten a worth of 0.056, it very well may be inferred that there is a huge connection among conviction and understudy learning results in math. The extent of the relationship is remembered for the medium class